Sintomatología depresiva asociada a dispepsia en estudiantes de medicina humana - Iquitos 2022 - Vasquez Mesias, Dan Lennin (2023)
It is estimated that in Loreto, there is a 37% prevalence of dyspepsia in young adults. Although this pathology is not fatal, it causes heavy state expenditures worldwide and a decrease in the quality of life of those who suffer from it. One of the main factors related to the presence of dyspepsia is depression and specific populations such as medical students are more predisposed to suffer from it. Therefore, the main objective of the present study was to determine the association between clinically relevant depressive symptomatology and uninvestigated dyspepsia in students from the second to the seventh level of the medical school of the Peruvian Amazon National University. This was a observational, descriptive and cross-sectional study, which included 206 students. A prevalence of 43.69 % of uninvestigated dyspepsia was found and it was higher in 6th-year students. In addition, 40.29% of students had clinically relevant depressive symptomatology. Regarding the main objective, it was found that the frequency of uninvestigated dyspepsia was higher among medical students who had clinically relevant depressive symptomatology (p<0.001). It is concluded that depressive symptomatology is associated with the presence of uninvestigated dyspepsia in medical students of the Peruvian Amazon National University.